An intimate glance into "The Holiest of Holies": An exploratory study of the half-time talk - Avugos, S.; Zach, S.; Dvir Malca, A.; Bar-Eli, M. (International Journal of Sport and Exercise Psychology, 2020)
Investigations of in-game coaches` comments and behaviours are scarce. An area of particular neglect has been that of the half-time coach-team interactions. This study addresses the half-time meeting and provides a glance at coach-team communication during this critical time in competition. Six male soccer coaches (aged 35-47) served as one data source. They all had substantial coaching experience and were actively coaching teams at the men`s Premier League. We also collected data from two other soccer coaches (age 39 and 46) at the under-21 league, who agreed to uncover their authentic talks. The post-game interviews and authentic audio recordings from the changing room revealed two main themes underpinning the coaches` pattern of behaviour: (a) largely using criticism, and (b) developing game understanding by technical and tactical content instructions. The results also show that coaches place a low value on the possibility that their half-time talk will significantly improve the players` morale and their performance later in the game. We suggest that the role of emotions in choices and decisions, and particularly the effect of emotional regret, might explain this attitude. More knowledge is required to assist sport psychologists in developing guidelines for coaches to effectively use their half-time talks.